2021
DOI: 10.1002/adfm.202108959
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of Defects in Ti3C2Tx and Ti3C2Tx‐Assisted Reduction of Graphene Oxide for Highly Selective Detection of ppb‐Level NO2

Abstract: At present, the main gas-sensing mechanism of oxidized MXene (Ti 3 C 2 T x ) is commonly regarded as Schottky barrier modulation, but the influence of surface defects generated by oxidation is ignored and ambiguous. Herein, oxidized Ti 3 C 2 T x crumpled spheres (MS) are obtained, accompanying numerous surface defects through thermal oxidation of MS synthesized by ultrasonic spray pyrolysis technology and gas-sensing properties of oxidized MS with Ti 3 C 2 T x /TiO 2 crumpled spheres (MT-10-1) without new surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 36 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Recently, Yang et al demonstrated the inherent process of the improvement of gas-sensing capabilities of oxidized Ti 3 C 2 T x by analyzing the performance of crumpled Ti 3 C 2 T x spheres. 113 This was done in order to show that the crumpled Ti 3 C 2 T x spheres have better gas-sensing properties. After explaining the structural and compositional modifications caused by the oxidation of Ti 3 C 2 T x , it was found that the increase in gas-sensing capabilities was due to the presence of a large number of Ti atom defects that had been introduced by the oxidation process.…”
Section: Application Of Ti3c2tx Mxene As a Gas Sensormentioning
confidence: 99%
“…Recently, Yang et al demonstrated the inherent process of the improvement of gas-sensing capabilities of oxidized Ti 3 C 2 T x by analyzing the performance of crumpled Ti 3 C 2 T x spheres. 113 This was done in order to show that the crumpled Ti 3 C 2 T x spheres have better gas-sensing properties. After explaining the structural and compositional modifications caused by the oxidation of Ti 3 C 2 T x , it was found that the increase in gas-sensing capabilities was due to the presence of a large number of Ti atom defects that had been introduced by the oxidation process.…”
Section: Application Of Ti3c2tx Mxene As a Gas Sensormentioning
confidence: 99%
“…Wherein, electrochemical gas sensors have been widely used in practice, with large volume, and high rigidity, and their development in wearable electronics has been stagnant. Although various novel materials such as transition metal dichalcogenide (TMD), metal-organic-framework, MXenes, organic-inorganic hybrid superlattices have been explored to construct NO 2 sensors with high sensitivity and low limit of detection (LOD), [17][18][19][20] a long-standing challenge for these sensors is their poor ductility under complex mechanical deformations even in combination with flexible substrates. Hydrogels are intrinsically stretchable solid-state materials with liquid-like ion transport capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…As a common gas in industrial production, nitrogen dioxide (NO 2 ) can lead to grave respiratory problems, including inflammation of the trachea and accumulation of fluid in the lungs. Moreover, recent investigations have shown that NO 2 is closely related to the prevention and transmission of COVID-19. , And it is also a significant account of environmental pollution such as summer smog, acid rain, and PM 2.5, which poses a major endangerment to mankind’s health and the safety of other life on the earth. , According to the OSHA regulations, the maximum concentration of short-term exposure to NO 2 is 5 ppm in industry. Long-term exposure to high concentrations of NO 2 can lead to poor breathing, lung disease, and even death. , Additionally, nitric oxide (NO) is a major contributor to air pollution and can have an unfavorable influence on mankind’s health.…”
Section: Introductionmentioning
confidence: 99%